(untitled) (Mwanga wa Lugha, 2022)
This paper investigates the occurrence of interjections as hedges in Kenya’s presidential political speeches and their translatability from English into Kiswahili from a skopos based perspective. These hedges have a significant pragmatic functionality that cannot be ignored even in translation. The paper explores the usage of this kind of a hedge in the presidential political speeches in Kenya and what effect arises from its translatability or non-translatability. As a communicative feature that carries an indirect meaning, hedges play a significant role in message delivery, a functionality that makes them important in a discussion. As opined by Lakoff (1972), hedges’ functionality is beyond the fuzzy notion, carrying an important meaning that would have otherwise not possible to deliver it devoid of these hedges. Pragmatically, this linguistic feature has been referred to in different terms such as shields, indeterminants and expression of politeness (Halliday 1994, Levinson 2000). In this regard, their functionality is a necessary ingredient in communication process which cannot be ignored. This research has been carried out in reference to Skopo’s theory whose tenetes of purpose, optimality, faithfulness and cohesion looks at the usage of these words and their transferability from English to Kiswahili in Kenyan’s political speeches since their presence in a communication process generally is and often has been viewed as nuisance. Twenty speeches from Kenya’s presidential candidates in 2013 and 2017 together with their running mates were transcribed. The units of meaning with interjections were identified and subjected to translation from English into Kiswahili. It was found that translation strategies largely used ware literal translation, omission and domestication although other approaches were still available in rendition of the required meaning.